Surface rehabilitation of Portland cement concrete (PCC) pavements using single or double surface dressings with soft bitumen, conventional or modified emulsions. (26th April 2021) - Rocha Segundo, Iran; Silva, Leonel; Palha, Carlos; Freitas, Elisabete; Silva, Hugo
Highlights: Single surface dressings increased more the macrotexture of concrete pavements. Soft bitumen performed better than emulsions when pulling-off surface dressings. Vialit mechanical adhesion was similar for conventional and modified emulsions. Double surface dressings covered with diluted emulsion wear less in the prototype. Surface dressings are potential surface treatment alternatives for concrete pavements. Abstract: Surface dressings are a sustainable maintenance alternative for pavements with surface distresses, due to the low amount of resources involved. This paper aims to analyze the viability of using twelve different surface dressing solutions, including three binders (conventional and modified emulsions, and a soft 160/220 bitumen) and a covering with diluted emulsion, for surface treatment of Portland cement concrete (PCC) pavements. Several test methods were used to evaluate the macrotexture, skid resistance, adhesion, and resistance to wearing on a large scale prototype. In general, single surface dressings increased further the macrotexture of the concrete pavement surface. The skid resistance of single and double surface dressings was similar. The best surface dressing in the pull-off test was that with the 160/220 bitumen. The conventional and modified emulsions presented similar mechanical adhesion in the Vialit plate test. Concerning the prototype wearing test, the best result was obtained for the double surface dressing with bitumen covered with diluted emulsion. Based on this work's results, the surface dressings are a potential surface rehabilitation alternative for concrete pavements.